Lipoprotein apheresis in patients with peripheral artery disease and lipoprotein(a)-hyperlipoproteinemia: 2-year follow-up of a prospective single center study. (November 2017) - Poller, Wolfram C.; Berger, Axel; Dreger, Henryk; Morgera, Stanislao; Enke-Melzer, Kathrin
Abstract: Objective: Elevated plasma levels of lipoprotein(a) [Lp(a)], referred to as lipoprotein(a)-hyperlipoproteinemia [Lp(a)-HLP], are an independent risk factor for atherosclerosis. Lipoprotein apheresis (LA) enables an effective reduction of Lp(a) plasma levels. The present study investigates the effects of LA in patients with Lp(a)-HLP and peripheral artery disease (PAD). Methods: Ten patients with isolated Lp(a)-HLP and severe PAD and who had recently undergone a revascularization (index procedure) were prospectively included in this observational single center study. All patients received weekly LA. Ankle-brachial-index (ABI), transcutaneous partial oxygen pressure (tcpO2 ), pain level, and walking distance were assessed at baseline and at the follow ups scheduled 1, 3, 6, 12, and 24 months after initiation of LA. The number of revascularizations within 12 months prior and within 24 months after the index procedure was determined. Results: As early as 1 month after initiation of LA, all investigated parameters had improved significantly compared to baseline. This improvement was further substantiated under LA throughout the entire follow-up period. Comparing baseline results with the 24-month follow-up, the average ABI increased from 0.53 ± 0.15 to 0.97 ± 0.08 ( P  < 0.001). The mean tcpO2 also increased from 42.9 ± 2.3 mmHg to 61 ± 4.6 mmHg ( P  < 0.001). The improved perfusion led to a reduction of the mean pain level from 7.0 ± 1.5 to 1.1 ± 0.4 ( P  < 0.001) on a visual analogue scale (VAS) and an extension of the mean walking distance from 87 ± 60 m to 402 ± 119 m ( P  < 0.001). All patients suffered from severe PAD with a high number of revascularizations in the 12 months prior to the index procedure (35 procedures in 120 patient-months). Since initiation of LA, the number of revascularizations dropped significantly and remained very low during the entire follow-up period (2 procedures in 229 patient-months, P  < 0.001). Conclusion: In patients with Lp(a)-HLP and severe PAD, LA results in sustained improvement of circulation, pain level and walking distance. The number of repeat revascularizations is strongly reduced under LA treatment.